THE EFFECT OF NATURAL FEED REPLACEMENT WITH ARTIFICIAL FEED ON THE GROWTH AND SURVIVAL RATE OF BLACK GHOST LARVAE (Apteronotus albifrons) - Sipayung, Kristin; Nuraini, Nuraini; Alawi, Hamdan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conduted on August until September in Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine University of Riau. The aim of this research was to know the effect of natural feed replacement with artificial feed on the growth and survival rate of Black Ghost Larvae (Apteronotus albifrons). The method in this research was an experimental method with Completely Randomized Design (CRD) with one factor, nine treatments and three replication. The treatment in this research were P1 (Artemia sp. for 40 days),P2 ( Tubifex sp. for 40 days), P3 ( Paste feed for 40 days), P4 ( Artemia sp. for 10 days + Paste feed for 30 days), P5 ( Artemia sp. for 20 days + Paste feed for 20 days), P6 ( Artemia sp. for 30 days + Paste feed for 10 days), P7 ( Tubifex sp. for 10 days + Paste feed for 30 days), P8 ( Tubifex sp. for 20 days + Paste feed for 20 days), P9 ( Tubifex sp. for 30 days + Paste feed for 10 days). The result showed that the best treatment was in P9( Tubifex sp. for 30 days + Paste feed for 10 days) the absolute weight growth was 0,492 grams, the absolute length growth was 4,34 cm  specific growth rate was  16,28 % dan survival rate was 94,4 %.Keyword : Artemia sp. Tubifex sp. Growth and Giant Black Ghost                              (Apteronotus albifrons).